Essays on art and science - Kandel, Eric R. 1929- (Columbia University Press, 2024)
"Eric Kandel collects a group of seven essays published between 2014 and 2020 into a new volume. He has revised them to reduce repetition across the volume--and in the case of one academic journal article, adapted the piece for a more general audience. Most of the essays come from art gallery catalogues, and so they are not readily available, especially to a neuroscience audience. The essays largely cover art history and artistic expression through the lens of brain science, with a focus on the concept of the "beholder's share"--that is, what the viewer contributes to a work of visual art by viewing it"--
Keywords: Kunst; Neurowissenschaften; Art / Psychology; Art / Psychologie; SCIENCE / Essays; SCI089000; SCIENCE / Life Sciences / Neuroscience